Pengembangan Sistem Absensi Mahasiswa Menggunakan Esp32 Berbasis Internet of Things - Prastya, Eka Putra; Misbah, Misbah (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
Muhammadiyah Gresik University is one of the educational institutions in Gresik City. At Muhammadiyah University of Gresik there are various faculties and study programs which are certainly not far from the student attendance registration system. Muhammadiyuah Gresik University uses an attendance registration system in the form of Manual Attendance and SPADA Digital Attendance. From this attendance system, fraud often occurs. Apart from these things, the Administration of the Faculty of Engineering also has several obstacles in managing student attendance data, namely that there are two types of attendance list management so that student attendance data must be managed twice through Manual attendance and SPADA Digital Attendance. And in both systems the number of attendance is not listed, so you have to calculate attendance manually. To overcome this, an attendance system update was carried out, namely using IoT-based Fingerprint using an ESP32 microcontroller. The work process in this attendance system is that the attendance system can be monitored in real-time and record student attendance efficiently. This system is processed by an ESP32 microcontroller which then manages the data using Google Spreadsheet in real-time. The results of implementing this system can be real-time monitoring of attendance, effective data management, and reducing the occurrence of fraud in student attendance.